2001
DOI: 10.1046/j.1523-1747.2001.01159.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Dendritic Cell Differentiation by Fumaric Acid Esters

Abstract: Fumaric acid esters have proved to be effective for the systemic treatment of severe psoriasis vulgaris. These compounds have been shown to induce a Th2-like cytokine secretion pattern in T cells and to reduce keratinocyte proliferation in vitro. Dendritic cells seem to be of major importance as regulatory cells driving the psoriatic tissue reaction. Monocytes or CD34-positive myeloid progenitor cells are precursors of dendritic cells that can be generated in vitro by culture with granulocyte-macrophage colony… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
92
1
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(99 citation statements)
references
References 24 publications
5
92
1
1
Order By: Relevance
“…For example, in lymphocytes, DMF and its hydrolysis product, methylhydrogen fumarate (MHF), modulated cytokine expression toward a Th2 cytokine profile (18,19). Both substances inhibited keratinocyte proliferation (20) and monocyte differentiation into dendritic cells (21).…”
mentioning
confidence: 99%
“…For example, in lymphocytes, DMF and its hydrolysis product, methylhydrogen fumarate (MHF), modulated cytokine expression toward a Th2 cytokine profile (18,19). Both substances inhibited keratinocyte proliferation (20) and monocyte differentiation into dendritic cells (21).…”
mentioning
confidence: 99%
“…Therefore, in another study we investigated the effects of MMF on the differentiation of monocytes to iDC (our unpublished data). Others already reported that DMF and MMF, but no other fumarates, affected monocyte-derived DC differentiation, as reflected by an inhibition of expression of various costimulatory molecules and a reduced capacity of DC to stimulate T cells [13]. The effects of a 24-h incubation of MMF on cytokine production by DC were dosedependent (maximal inhibitory effect with 100 ?…”
Section: Discussionmentioning
confidence: 92%
“…Since others have reported that high concentrations of DMF may induce apoptosis of cells [13], we first investigated the effect of incubation of monocyte-derived iDC for 24 h with increasing concentrations of MMF on cell viability. FACS analysis revealed that MMF at concentrations up to 100-200 ?…”
Section: Effect Of Mmf On Cytokine Production By DCmentioning
confidence: 99%
See 1 more Smart Citation
“…Auch die deutliche Hemmung der Produktion pro-entzündlicher Zytokine durch DMF wurde beschrieben [305]. Interessanterweise hemmen DMF und MHF die Reifung von dendritischen Zellen, denen bei der Entstehung und Unterhaltung der Immunreaktion bei der Psoriasis vulgaris eine wesentliche Bedeutung zugeschrieben wird [306]. Ältere Arbeiten haben für MHF in vitro an aktivierten T-Zellen die Verschiebung der Sekretion von Th1-artigen Zytokinen zu Th2-artigen beschrieben [307][308][309] [315,319].…”
Section: Zeitraum In Monatenunclassified